Pattern recognition and information processing : 14th International Conference, PRIP 2019, Minsk, Belarus, May 21-23, 2019, Revised Selected Papers /: 14th International Conference, PRIP 2019, Minsk, Belarus, May 21-23, 2019, Revised Selected Papers. (2019) - Unknown
No abstract available